Špancirfest - Street Strollers' Festival in Varaždin - Kelemen, Petra (2008)
The paper focuses on a contemporary Croatian urban festival - Špancirfest - Street Strollers' Festival in Varaždin. It analyzes main ideas of organizers and its main goals. On one hand, it stresses the festival importance in tourist context, and on the other hand, the connection between the festival and the town identity.
Projekt MZOS
ENG